Faktor – Faktor Yang Berhubungan Dengan Kepuasan Kerja Perawat Di Instalasi Rawat Inap Rumah Sakit PKU Muhammadiyah Yogyakarta: Factors Associated with Nurse Job Satisfaction in the Inpatient Unit of PKU Muhammadiyah Hospital Yogyakarta - Lisdiyanti, Teti; Syam, Nur Syarianingsih (Universitas Ahmad Dahlan, 2023)
Background: As many as 40% of healthcare workers in Indonesia are nurses. Nursing services are a determining factor in the success of health services that impact the quality of hospital services. Therefore, improving service quality is related to the level of nurse job satisfaction. Objective: The purpose of this study is to identify factors related to nurse job satisfaction in the Inpatient Installation of PKU Muhammadiyah Yogyakarta Hospital. Methods: This study applied a Cross-Sectional research design, conducted in July 2023 at PKU Muhammadiyah Yogyakarta Hospital. The research sample was inpatient nurses with a total sampling technique of 175 nurses. Researchers collected data by distributing questionnaires. In analyzing the data, univariate analysis with frequency distribution and bivariate analysis with Chi-Square test were used. Results: The job itself is related to inpatient nurse job satisfaction, indicated by a p-value of 0.000 (p <0.05) Salary and inpatient nurse job satisfaction are related, indicated by a p-value of 0.000 (p <0.05). Job promotion is related to inpatient nurse job satisfaction, indicated by a pvalue of 0.000 (p <0.05). Conclusion: This study concluded that nurses' job satisfaction needs to be maintained and improved through nurse career development programs and appropriate work benefits.